OPTIMALISASI PERAN BADAN USAHA MILIK DESA (BUMDES) SINGAJAYA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS DI DESA BODAS KECAMATAN WATUKUMPUL) - Novita Riyanti; hendri hermawan Adinugraha (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
Village development is one of the goals for equitable distribution of national development which has long been scheduled by the government, this is because villages still dominate poverty in Indonesia. One of the efforts made by the government for the welfare of rural communities is by establishing village-owned enterprises throughout Indonesia. The establishment of the Singajaya BUMDes was in accordance with Pemalang district regulation No. 9 of 2007 concerning Guidelines for the Establishment of Village-Owned Enterprises. The establishment of the Singajaya BUMDes aims to participate in village development and provide services to the community in its management carried out by the village government and the community. The existence of the Singajaya village-owned enterprises (BUMDes) is expected to be able to improve the village economy to create community welfare. The purpose of this study was to determine whether the role of the Singajaya BUMDes was optimal for the welfare of the village community or not. This research is a qualitative research with a descriptive approach. The results showed that the Singajaya BUMDes has played a role in improving the welfare of the community, but it has not been optimal in its implementation, the factors that become obstacles in running a business are limited human resources, weak managerial capacity and low capital. So the government's role is needed to conduct socialization and provide training and assistance to the community regarding the management of the Singajaya BUMDes so that it can be carried out properly and professionally.